2003
DOI: 10.1055/s-2003-38295
|View full text |Cite
|
Sign up to set email alerts
|

Foker's Technique in Oesophageal Atresia with Double Fistula: A Case Report

Abstract: The authors' starting point is a new surgical approach described by Foker and performed by them on a newborn with long-gap oesophageal atresia. We discuss the possibility of obtaining rapid growth of the atretic oesophagus and performing a primary anastomosis in the case of long-gap oesophageal atresia. With this procedure, primary oesophageal repair could be performed without myotomies, without flaps and with the gastrooesophageal junction below the diaphragm. The need for gastrostomy would be also eliminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Similarly to several surgical techniques used for esophageal elongation (1)(2)(3)(4)(5)(6)(7)(8)(11)(12)(13)(14)(15)(16)(17), in this study the esophagus was elongated by traction as well. To the best of our knowledge, this is the first study to clarify which part of the esophagus was elongated by traction.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly to several surgical techniques used for esophageal elongation (1)(2)(3)(4)(5)(6)(7)(8)(11)(12)(13)(14)(15)(16)(17), in this study the esophagus was elongated by traction as well. To the best of our knowledge, this is the first study to clarify which part of the esophagus was elongated by traction.…”
Section: Discussionmentioning
confidence: 94%
“…Esophageal elongation by traction suture has been used for the management of long-gap esophageal atresia (EA) in pediatric patients (1)(2)(3)(4)(5)(6)(7)(8)). Foker's method is one of the surgical techniques used to elongate the esophagus.…”
Section: Introductionmentioning
confidence: 99%
“…However, this did not prevent pneumothorax and leakage in several studies [2,3]. The main problem was that the traction sutures usually cut through the esophagus and cause leakage and disruption of traction [2][3][4][5][6][7]. Some authors suggested the use of pledgeted sutures to eliminate shear at the tissue-suture junction.…”
Section: Discussionmentioning
confidence: 99%
“…It is still the opinion of most surgeons that the native esophagus is the best conduit [1]. There have been several reports in infants with long gap esophageal atresia of successful mechanical esophageal elongation using Foker technique and its application in clinical practice [2][3][4][5][6][7]. The major drawback with this technique is that the traction sutures may cut through the esophagus in many cases [2,3].…”
mentioning
confidence: 99%
“…68 Currently, the Foker procedure, or its modifications, has been successfully used in more than 100 infants with LGEA worldwide. 54,[67][68][69][70][71][72] In the largest single author experience on 63 consecutive patients with a gap greater than 2.5 cm, the ET allowed primary repair of the esophagus in all cases within 3-31 days (mean 14 7 7 days), with a rate of gap shortening of 0.53 7 0.2 cm/day. 73 In 16% of patients, a further thoracotomy was required to either reconfigure or replace traction sutures.…”
Section: Traction and Growthmentioning
confidence: 99%